A bandage contact lens prevents extrusion of ocular contents. Issue 1 (February 2016) - Ramjiani, Vipul; Fearnley, Thomas; Tan, Jennifer
Abstract: A 76 year old male presents with a corneal perforation in a phthisical eye. Definitive treatment in the form of an evisceration was delayed by 38 days. During this period a bandage contact lens prevented extrusion of ocular contents through an enlarging corneal perforation. This case demonstrates that a bandage contact lens can be effective in the immediate management of large corneal perforations whilst awaiting urgent definitive treatment.